CREB binding protein acts synergistically with steroid receptor coactivator-1 to enhance steroid receptor-dependent transcription. - Smith, C L (1996)
Steroid receptors are ligand-regulated transcription factors that require coactivators for efficient activation of target gene expression. The binding protein of cAMP response element binding protein (CBP) appears to be a promiscuous coactivator for an increasing number of transcription factors and the ability of CBP to modulate estrogen receptor (ER)- and progesterone receptor (PR)-dependent transcription was therefore examined. Ectopic expression of CBP or the related coactivator, p300, enhanced ER transcriptional activity by up to 10-fold in a receptor- and DNA-dependent manner. Consistent with this, the 12S E1A adenoviral protein, which binds to and inactivates CBP, inhibited ER transcriptional activity, and exogenous CBP was able to partially overcome this effect. Furthermore, CBP was able to partially reverse the ability of active ER to squelch PR-dependent transcription, indicating that CBP is a common coactivator for both receptors and that CBP is limiting within these cells. To date, the only other coactivator able to significantly stimulate receptor-dependent transcription is steroid receptor coactivator-1 (SRC-1). Coexpression of CBP and SRC-1 stimulated ER and PR transcriptional activity in a synergistic manner and indicated that these two coactivators are not functional homologues. Taken together, these data suggest that both CBP and SRC-1 may function in a common pathway to efficiently activate target gene expression.